(3fXQjI GdeMGSHIs - (3MSjf(B, (3GdbGVjs; (3eCehf MeOGf(B, s ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B,s, 2012)
(3GdfXQjI ef efXhQ JGQjNj(B- (3GdWHjYI GdYdejI ddeMGSHI(B- (3eaghe GdTNUjI GdeYfhjI(B- (3eaghe GdfXGe GdeMGSHj(B- (3eaghe GdGMOGK GdEbJUGOjI(B- (3eaghe GdEaUGM(B- (3ehVhYjI GdbjGS(B- (3eHGOF GdeMGSHIs
(3GdeQGLY U(B.547 (3GdedGMb U(B. 525s
Keywords: (3GdeMGSHIs; (3GdeMGSHI(B- (3fXQjGJs